(3GdhSjW aj TQM LQGFe GdHdWLI (B:s (3WHbG ddbGfhf Qbe (B02 (3dSfI (B1998 (3aj VhA CQGA GdabgG hCMcGe GdbVGA (B/s - (3GdYGOdj, eMehO UGdMs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2000)
(3aj gPG GdcJGH (B: (3GdHdWLI ,GdQcf GdeGOj ,UhQ GdHdWLI ,GdbhI hGdYfa ,GdJYQa, GdJgOjO , GdfJjLI GdELQGeI , GdfJGFL GdeOjI , GdfJGFL GdeYfhjI , QGHWI GdHfjI ,GdQcf GdeYfhj hGdYbhHI ,GdCMcGe GdYGeI ddbUO GdLfGFj , LQGFe GdHWLI GdeTOOI , LfM GdHdWLI GdeTOOI ,GdXQha GdeJYdbI HGdLGfj hGdeLfj Ydjg , JYOO GdLfGI ,GdEQJHGW hJYOO GdLfGI ,EQJHGW GdHdWLI HLQjeI GdEjPGA hGdbJd GdYeOjs
(3GdeQGLY U(B.161s
Keywords: (3GdLQjeI hGdeLQehf(B-(3eUQs; (3GdbGfhf GdLfGFjs; (3bhGfjf hJTQjYGJs